1997
DOI: 10.1089/neu.1997.14.629
|View full text |Cite
|
Sign up to set email alerts
|

Transiently Increased Basilar Artery Flow Velocity following Severe Head Injury: A Time Course Transcranial Doppler Study

Abstract: A significant number of patients develop increased flow velocities compatible with vasospasm in the basilar artery after severe head injury. This phenomenon may represent an additional factor that contributes to the poor outcome of severely head-injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…PTV has also been associated with the presence of intracranial hemorrhage following TBI [8,12,17,31,32,41], but the distribution of that hemorrhage varies among studies. For example, Hadani et al [8] found the incidence of PTV in the anterior or posterior circulation increased from 43% to 58% if traumatic subarachnoid hemorrhage (tSAH) was present.…”
Section: Posttraumatic Cerebral Artery Vasospasmmentioning
confidence: 99%
See 4 more Smart Citations
“…PTV has also been associated with the presence of intracranial hemorrhage following TBI [8,12,17,31,32,41], but the distribution of that hemorrhage varies among studies. For example, Hadani et al [8] found the incidence of PTV in the anterior or posterior circulation increased from 43% to 58% if traumatic subarachnoid hemorrhage (tSAH) was present.…”
Section: Posttraumatic Cerebral Artery Vasospasmmentioning
confidence: 99%
“…For example, Hadani et al [8] found the incidence of PTV in the anterior or posterior circulation increased from 43% to 58% if traumatic subarachnoid hemorrhage (tSAH) was present. Romner et al [15] found anterior circulation PTV incidence increased from 28% to 41% with tSAH, a correlation that has been further supported by other authors as well [12,24,31,32].…”
Section: Posttraumatic Cerebral Artery Vasospasmmentioning
confidence: 99%
See 3 more Smart Citations